An Economic Analysis of the Social Grant Policy in South Africa - GARIDZIRAI, Rufaro; CHIKURUWO, Rufaro Emily (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).09, 2020)
South Africa`s economy is largely influenced by socio-economic challenges that need attention. These challenges include poverty, stagnant economic growth, unemployment and crime. In a bid to address these challenges, the Constitution of the Republic of South Africa established the social grant system as one of the solutions to the above entrenched challenges. Section 27 (1) (c) of the Constitution affords everyone the right to social security, including, appropriate social support for themselves and those that depend on them. The critical question is whether the social grant system can solve all the above-mentioned challenges? This question remains as one of the unanswered questions in South Africa’s policy space. Extensive examination of this conundrum is therefore necessary. Thus, the objective of this study is to investigate whether the social grants are economically sustainable in South Africa. The study utilized a combination of the doctrinal research methodology and literature review approach in achieving the objective of the study. The results of the study suggest that the social grant system is a short-term policy that presents long-run challenges, especially if the economic outlook of the country is not favorable. Therefore, although the social grant system is legally supported by the Constitution, it is nonetheless economically unsustainable considering the economic metrics of South Africa. Based on the results of the study, the paper proposes that the government introduces a new system of social grants that promotes small businesses for citizens so that they do not rely on the government for survival.